2022
DOI: 10.1002/elan.202200159
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Tau Protein Immunosensor Based on MnS/GO/PANI and Magnetite‐incorporated Gold Nanoparticles

Abstract: Herein, electrochemical tau protein immunosensor based on manganese sulfide nanoparticles/graphene oxide/polyaniline (MnS/GO/PANI) and magnetiteincorporated gold nanoparticles (AuNPs@Fe 3 O 4 ) was constructed. After the modification of the glassy carbon electrode (GCE) with MnS/GO/PANI, the immobilization and conjugation of anti-Tau capture antibody and antigen Tau protein were successfully completed on MnS/GO/ PANI/GCE, respectively. Then, the conjugation of anti-Tau secondary antibody was carried out to AuN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 81 publications
(73 reference statements)
0
15
0
Order By: Relevance
“…Lately a tau protein immunosensor based on manganese sulphide (MS) graphene oxide (GO) and PANI (MnS/GO/PANI) with magnetite-incorporated gold nanoparticles immunosensor has been developed for the electrochemical detection of tau protein which exhibited superior selectivity, sensitivity, and environmental compatibility. 42 The sensor demonstrated the a detection limit of 1.0 × 10 −14 M which could be utilized for diagnosis of Alzheimers disease. Park et al 43 designed an aptasensor based on PANI and carbon nanotube (CNT) for detecting VEGF165 as a tumor marker with a limit of detection of 0.4 pg mL −1 and showed high selectivity in presence of other proteins.…”
Section: Applications In Protein Detectionmentioning
confidence: 99%
“…Lately a tau protein immunosensor based on manganese sulphide (MS) graphene oxide (GO) and PANI (MnS/GO/PANI) with magnetite-incorporated gold nanoparticles immunosensor has been developed for the electrochemical detection of tau protein which exhibited superior selectivity, sensitivity, and environmental compatibility. 42 The sensor demonstrated the a detection limit of 1.0 × 10 −14 M which could be utilized for diagnosis of Alzheimers disease. Park et al 43 designed an aptasensor based on PANI and carbon nanotube (CNT) for detecting VEGF165 as a tumor marker with a limit of detection of 0.4 pg mL −1 and showed high selectivity in presence of other proteins.…”
Section: Applications In Protein Detectionmentioning
confidence: 99%
“…Voltammetry is an electro-analytical method, based on current-voltage and concentration relations, which provides information about the analyte by measuring the current at the applied potential in conditions where the working electrode is polarized. 7,8 Thus, this method can provide important contributions in the eld of health and nutrition by identifying and eliminating the possible negative effects of HMF on the health of living organisms, especially humans.…”
Section: Introductionmentioning
confidence: 99%
“…These carbon materials and their hybrid composites have been widely used in the study and development of a variety of novel biosensors and immunosensors. [21][22][23][24][25][26] From the literature survey, it is observed that functionalized graphene oxide, reduced graphene oxide, carbon nanotubes, and graphitic carbon nitride have also been used for the detection and determination of 2-CP or 2,4-DCP individually. Functionalization was performed mainly by incorporating metal, metal oxide nanoparticles, metal-organic frameworks, or cyclodextrins.…”
Section: Introductionmentioning
confidence: 99%